Hubungan Antara Motivasi Berprestasi Dengan Adversity Quotient Pada Remaja - Octavianti, Prasti; , Dra. Wiwin Dinar P., M.Si (2016)
Adversity quotient is an intelligence of an individual in overcoming difficulty and being able to survive, or in other words, unflinching in facing every problem of life. Adversity quotient means persistence or perseverance of an individual when he or she is facing problems.Purposes of the research are to: 1) know correlation between motivation of achieving and Adversity quotient; 2) see level of adversity quotient of students in SMA 2 Sukoharjo; 3) know level of motivation of achieving of the high school students. Hypothesis of the research is: "there is a positive correlation between motivation of achieving and adversity quotient of adolescents." Subject of the research was 3th grade students of SMA 2 Sukoharjo amounting to 88 persons. Sample of the research was taken by using cluster random sampling. Instruments of the research were scale of motivation of achieving and adversity quotient scale. Data was analyzed by using product moment correlation. Based on data analysis, it can be known that a significant positive correlation was found between motivation of achieving and adversity quotient, showed by (r) value = 0.720, and p = 0.000 (p<0.01). Based on values obtained, the achieving motivation variable had mean empiric of 98.51 and mean hypothetic of 90 meaning that the subjects had high tendency in the motivation of achieving. Adversity quotient variable had mean empiric of 93.80 and mean hypothetic of 82.5 meaning that the subjects had very high adversity quotient. Effective contribution of variable of the motivation of achieving to adversity quotient was 51.8%. It was indicated by determinant (r2) = 0.518.